Estudo sobre a reciclagem de fibras têxteis - Sato, Ian Hideyuki Fugitani (Universidade Federal de São Carlos, 2022)
In order to transform the textile industry into something sustainable, the origin and production must be studied, and in addition, it is expected that there will be a greater importance of recycled products in the future, since there is concern about the scarcity of raw material that has become a recurring theme in recent times. Recycling textile fibers is still in its infancy and will still face several challenges to consolidate and become a recurrent practice. In order to add, this work compiles knowledge that helps textile recycling, being one of the points addressed the classification of fibers suggesting that the fibers are separated aiming at their chemical characteristics and not their origin approaching how the recycling of polymers is done. We also address some problems already faced in textile recycling such as mixed fibers and study new methods that are being developed little by little, such as biological degradation. And we briefly discussed how textile fiber recycling is in Brazil. Based on the authors used with reference, we conclude that it is an activity with great potential and that has been showing great economic and environmental importance
Study on the recycling of textile fibers
Keywords: Tecido; Reciclagem; Moda circular; Sustentabilidade; Processos enzimáticos; Textile; Recycling; Circular fashion; Sustainability; Enzymatic processes; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS